2000
DOI: 10.1007/pl00011692
|View full text |Cite
|
Sign up to set email alerts
|

Screening for gastric cancer in Japan

Abstract: In Japan, mass screening for gastric cancer with photofluorography was initiated in 1960. At present, over 6 million people are screened annually. The sensitivity and specificity of photofluorography are 70%-90% and 80%-90%, respectively. The 5-year survival rate is 15%-30% better in screendetected cancers than in symptom-diagnosed cases. Although no randomized controlled trials have been reported, cohort and case-control studies generally showed a decreased risk of mortality from gastric cancer in the screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 24 publications
2
90
0
6
Order By: Relevance
“…Regular screening has been shown to reduce long-term cancer mortality, (16,17) and a similar reduction or improvement of the prognosis for survival has been reported for GC. (9,18) Despite the importance of having routine cancer screening at the recommended intervals, there have been no published studies that have examined how many people attend repeat GC screening. An important goal of screening programs is not only to achieve high participation rates for the screening programs, but also to maintain these high rates at each subsequent round of screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regular screening has been shown to reduce long-term cancer mortality, (16,17) and a similar reduction or improvement of the prognosis for survival has been reported for GC. (9,18) Despite the importance of having routine cancer screening at the recommended intervals, there have been no published studies that have examined how many people attend repeat GC screening. An important goal of screening programs is not only to achieve high participation rates for the screening programs, but also to maintain these high rates at each subsequent round of screening.…”
mentioning
confidence: 99%
“…(5,7) In recent years, endoscopy has replaced photofluorography as the initial mass screening method in several cities in Japan. (8,9) This technique is increasingly useful for GC screening because of its high detection rate. In a study conducted in Niigata, Japan, the detection of GC by endoscopy was 2.7-4.6 times higher than that by direct or indirect UGIS.…”
mentioning
confidence: 99%
“…The rate of secondary examination in the GI X-ray group was slightly higher than the average rate reported by the Japanese Society of Gastroenterology Cancer Screening. However, considering the mean age of the subjects in this RCT, the rate may not be so high compared to the number of Japanese citizens in their 60 0 s. In Japan GI X-ray using a barium meal is the method for mass gastric cancer screening and is available to asymptomatic individuals older than 40; this is the established nationwide program [8]. Upon positive findings in the barium meal examination [30] further investigation with GIE is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 3 case-control studies showed that screening by GI X-ray results in reduced mortality from gastric cancer [8]. Thus, Japanese guidelines established in 2006 recommended the population undergo gastric cancer screening using GI X-ray [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The therapy of this cancer is early extirpation, whose outcome is closely related to the stage of disease progression. Japan, the country with the highest incidence in the world, has been broadly using X-ray screening to pick early gastric tumours since the 1960s (Inaba et al, 1999;Tsubono and Hisamichi, 2000). Some pilot programmes elsewhere sporadically used this Japanese technique as well (Llorens, 1991;Pisani et al, 1994).…”
mentioning
confidence: 99%